Théories géologiques et représentations du paysage dans la première moitié du xixe siècle - Alexis Drahos (Projets de Paysage)
From the final years of the eighteenth century, Geology enjoys a rapid development whose consequences won’t take long to react on the landscape painting of the time. Leaving from then on the study for the outer world, Naturalists set to look for clues on the ground to understand the past of our planet and particularly his old age. Artists imitate their reasoning and are fascinated as well by the naturals phenomenon like the volcanoes, the glaciers or simply the cliffs. Under the prism of the discoveries made in geosciences, it will be a matter to determine the influence of some scientific theories on the landscape painting. These doctrines will contribute to modernize this pictorial genre still too blocked by the tradition. Personalities such as Humboldt, Agassiz, Hutton and Cuvier have with their ideas profoundly changed the vision of our planet about his history, his evolution and his mechanisms. Our study which tackles some aspects of the geosciences like glaciology a paleontology will try to bring to the fore the range of these new scientific disciplines on the development of the landscape painting from the final years of the eighteenth century to the 1860 years.